Augmented Reality Experience in an Architectural Design Studio - Alp, Neşe Çakıcı; YAZICI, YASEMİN ERKAN; Öner, Dilan (Springer, 2023)
Thanks to the developing technology, different methods and tools are used in architectural representation, and architects contribute to developing these tools. Architects can easily model their designs with computer technologies and even make them visible in the environment with augmented reality technologies. Also, it is thought that these technologies will become widespread in basic architectural education over time. This study conducted a practice at the undergraduate architecture level using augmented reality technology. Within the scope of the study, the predisposition of students who experience augmented reality technologies to new representation, gender, course period, familiarity with playing computer games, the effect of computer programs that they can use in their previous augmented reality experience and designs if any, and the correlation between them has been tried to be revealed with this study. In this context, a study was carried out with thirteen students in the architectural design studio. Students were expected to parametrically design indoor exhibition elements using Rhinoceros 3D software and the Grasshopper plugin in the study. Then, an experimental augmented reality study was conducted with the Fologram, in which the students transferred these virtual exhibition elements they designed to the real indoors and reshaped them according to the space. Afterwards, a questionnaire consisting of five independent and ten dependent variables was applied to the students. The survey results were analysed with the IBM SPSS Statistics program. According to the results obtained, significant results were determined between 4 independent variables and one dependent variable.
Keywords: Augmented Reality (AR); Digital Experience; Fologram